Preventing opioid prescription after major surgery: a scoping review of opioid-free analgesia. (November 2019) - Fiore, Julio F.; Olleik, Ghadeer; El-Kefraoui, Charbel; Verdolin, Bernardo; Kouyoumdjian, Araz; Alldrit, Allison; Figueiredo, Ana G.; Valanci, Sofia; Marquez-GdeV, Javier A.; Schulz, Matthew; Moldoveanu, Dan; Nguyen-Powanda, Philip; et al.
Abstract: Background: Excessive opioid prescribing after surgery has been recognised as a contributor to the current crisis of opioid addiction and overdose. Clinicians may potentially tackle this crisis by using opioid-free postoperative analgesia; however, the scientific literature addressing this approach is sparse and heterogeneous, thereby limiting robust conclusions. A scoping review was conducted to systematically map the extent, range, and nature of the literature addressing postoperative opioid-free analgesia. Methods: Eight bibliographic databases were searched for studies addressing opioid-free analgesia after a major surgery. We extracted the study characteristics, including design, country, year, surgical procedure(s), and interventions. Results were organised thematically according to surgical specialty and targeted phase of recovery: in hospital (early recovery, ≤24 h after operation; intermediate recovery, >24 h) and post-discharge (late recovery). Reporting was according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement for scoping reviews. Results: We identified 424 studies addressing postoperative opioid-free analgesia. The number of studies conducted in countries where the opioid crisis is primarily focused was remarkably low (USA, n =11 [3%]; Canada, n =5 [1%]). Many RCTs compared opioid-free vs opioid analgesia during hospital stay ( n =117), but few targeted analgesia post-discharge ( n =8). Studies were predominantly focused on procedures in orthopaedic, general, and gynaecological/obstetric surgery. Limited attention has been directed towards non-pharmacological pain interventions. We did not identify knowledge synthesis studies (i.e. systematic reviews and meta-analyses) focused on the comparative effectiveness of opioid-free vs opioid analgesia. Conclusions: Opioids remain a mainstay analgesic for managing pain after surgery, but alternative analgesia strategies should not be overlooked. This scoping review indicates numerous opportunities for future research targeting opioid-free postoperative analgesia. Review registration: http://www.researchregistry.com ; ID: reviewregistry576.